2022
DOI: 10.3390/agronomy12051117
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate Fertilization Preserves Tomato Fruit Nutritional Quality

Abstract: Sulfur is an essential mineral in human nutrition, involved in vital biochemical processes. Sulfur deficient soil is becoming a severe issue, resulting from increased agricultural production and decreased sulfur emissions. Tomato cultivation using sulfur-poor soils and desalinated water is becoming widespread, and might result in plant and fruit sulfur deficiency. In the current work, we aimed at evaluating the effect of sulfur fertilization (0.1–4 mM) on fruit sulfur concentrations, under both low (4 mM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…It has been convincingly demonstrated that sulfur exerts a positive influence on the accumulation of total phenols and flavonoids, compounds known for their potent antioxidant properties and remarkable nutraceutical value. Our data corroborate the findings of numerous other researchers, underscoring how sulfur fertilization not only augments total phenols and flavonoids in sulfur-loving crops such as garlic [30], cabbage [31], onion [32,33], and broccoli [25], but also in other species like artichoke [34] and tomato [35].…”
Section: Ctrsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been convincingly demonstrated that sulfur exerts a positive influence on the accumulation of total phenols and flavonoids, compounds known for their potent antioxidant properties and remarkable nutraceutical value. Our data corroborate the findings of numerous other researchers, underscoring how sulfur fertilization not only augments total phenols and flavonoids in sulfur-loving crops such as garlic [30], cabbage [31], onion [32,33], and broccoli [25], but also in other species like artichoke [34] and tomato [35].…”
Section: Ctrsupporting
confidence: 92%
“…A recent manuscript [43] evidenced the important involvement of flavonoids in inflammatory response, highlighting their contribution to pathological pain by promoting plastic changes in the periphery and central nervous system, which in turn modify the neuronal phenotype and function. In particular, it was well demonstrated that these flavonoids diminished the neutrophil infiltration, had anti-inflammatory effect inhibiting cytokines, and antioxidant activity scavenging hydroxyl radicals; additionally, they also showed effects comparable to the corticoid prednisolone [35][36][37][38]. Pan et al [39] evidenced that the quotidian consumption of flavonoid-rich foods was able to cause beneficial changes in the gut microbiota, diminishing the risk of cancer and normalizing vital functions at the cellular level [40].…”
Section: Ctrmentioning
confidence: 99%